Analisis Strategi Pemasaran Untuk Meningkatkan Volume Penjualan Pada UMKM Akar Kelapa Mpok Nini Oleh-oleh Khas Betawi Di Bekasi - Handayani, Dewi; Firmansyah, Ade (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This study aims to analyse marketing strategies to increase sales volume at MSMEs of coconut roots Mpok Nini typical Betawi souvenirs located at Damri Bus Terminal in Bekasi. This research used a descriptive qualitative approach. Data collection techniques used are interviews, observation and documentation methods. Determination of informants based on owners and employees of MSMEs of coconut root Mpok Nini typical Betawi souvenirs, buyers of coconut root of MSMEs Mpok Nini typical Betawi souvenirs, and determination of academic lecturer informants selected based on Business Administration courses at the STIAMI Institute of Social and Management Sciences. The informants selected were 2 people from the coconut root of MSMEs Mpok Nini typical Betawi souvenirs, 2 buyers from the coconut root of MSMEs Mpok Nini typical Betawi souvenirs, and 1 academic lecturer informant Interview questions based on the marketing mix of the 4P marketing strategy, namely Product, Price, Place, Promotion. Based on these dimensions, there is each indicator to be used as a question in the interview. The 4P marketing strategy has been implemented by MSMEs of coconut root Mpok Nini typical Betawi souvenirs, product by maintaining excellence, price with affordable selling prices, place available in marketplaces and offline stores, and promotion carried out through marketplace advertisements. Obstacles in implementing marketing strategies are the emergences of competitors selling the same products and similar packaging.